DEPOSIT AND FINANCING INSTRUMENTS THROUGH WAQF BANK FOR FOSTERING REAL ECONOMY AND SOCIAL SUSTAINABILITY - Ab. Aziz, Muhammad Ridhwan; Yusof, Mohd Asyraf (UNISSULA, 2019)
During the global financial crisis and its aftermath, Islamic financial institutions were less affected, protected by their fundamental operating principles of risk sharing and the avoidance of leverage and speculative financial products. This has led to a greater appreciation of the role of Islamic finance in supporting economic growth across the globe. The contribution of Islamic finance and Islamic social finance especially through waqf sector promotes real economic development and could help to foster real economy and social sustainability.Â The impact and contribution of waqf for economic development in fostering real economy and social sustainability can be obverved in many areas such as enhancing economic progress, eradicating proverty, restoring distribution of income, reducing government expenditure, preventing deficit financing and stimulate growth and job creation. Therefore, a new mechanism is needed to support non-bankable and poor customers for financing facilities via Shariah compliant Islamic financial products and services.The purpose of this paper is to examine the most feasible mechanism for deposit and financing instruments based on waqf through Waqf Bank that able to foster and stimulate economic and social sustainability in the real economy sector especially for Muslim countries. The methodology of research in this study is through qualitative research based on interviews with Muslim scholars as well as Islamic banking and waqf practitioners. The finding of this study shows that there is feasible mechanism and modus operandi for the development of deposit and financing instruments in the Waqf Bank that able to be applied in many Muslim countries worldwide.